Two-layer remote phosphor package as a solution to promote color quality scale and lumen in WLEDs - Phuc Dang Huu; Dieu An Nguyen Thi (Bulletin of Electrical Engineering and Informatics, 2022)
This article demonstrates the influence of the red-light LaAsO4:Eu3+ phosphorus on the optical features of the two structures: one-layer remote phosphorus scheme (SRPS) and two-layer remote phosphorus scheme (DRPS). As a result, the Mie hypothesis is used to demonstrate and prove the comparison between color quality and luminosity (LF) between these two factors. The SRPS is a phosphor layer that consists of LaAsO4:Eu3+ particles combined with the YAG:Ce3+ mixture. Meanwhile, DRPS is two phosphor layers of red and yellow separated from each other. To improve the dispersing property, 5% of SiO2 is combined with the phosphorous films. The difference between the structures influences the optical features of WLEDs. The obtained outcomes show that the color rendering index (CRI) rises along with the concentrations of both structures while these values are nearly identical to each other. Meanwhile, at ACCTs (5600 K - 8500 K), the color quality scale (CQS) in DRPS reaches 74, which is higher than SRPS's 71 at 8500 K. Besides, the lumen in DRPS is considerably greater than that in SRPS at 2%-14% LaAsO4:Eu3+. In short, DRPS brings considerable benefits to the color quality and lumen when compared to SRPS. In addition, choosing a suitable concentration also becomes highly vital to achieve desirable CQS and LF.